A Wideband High-Gain All-Metal Antenna under Quad Resonances Realized by Folding a Simple Patch - Mohammad Hadi Moradi Aredekani; Aliakbar Dastranj; Seyyed Mohammad Bornapour (Journal of Electromagnetic Engineering and Science)
This paper presents a novel wideband antenna with a simple structure comprising an integrated microstrip patch antenna (MPA) and three shorted microstrip patch antennas (SMPAs). These four radiators constitute an antenna that operates under quad resonances and achieves a wide frequency bandwidth. Since all units are electrically connected, the antenna can be easily fabricated by folding a single metallic strip to realize an all-metal antenna structure, leading to enhanced resistance to extreme environmental conditions and lower power loss. An antenna prototype was used to validate the proposed concept. The measurement results indicated that the proposed handmade structure, which employed probe excitation with overall electrical dimensions of 0.29λ × 0.27λ × 0.11λ, can acquire an impedance frequency bandwidth of 67% for S11 ≤ −10 dB from 1.6–3.2 GHz and achieve a maximum boresight gain of up to 10 dB. The wide frequency bandwidth, high gain, and simple structure make this antenna a promising candidate for wideband mobile systems.